The Effect Of Using Online Articles On Students’ Reading Skill - Ayu RizkiRamadani; Ashari PSwondo (Journal MELT (Medium for English Language Teaching), 2022)
This research aimed to find The Effect of Using Online Articles on Students’ Reading Skill. This research is a quantitative study that used an experimental design. All Eighth grade students at SMP Budi Agung Medan are the population of this research. The samples used were class VIII-1 and VIII-2 SMP Budi Agung Medan, 30 students as the control group and 30 students as the experimental group. The instrument of this research were pre-test and post-test. The data that obtained from test analyzed by using SPSS. The result of this research showed that the mean scores of post-test was 58.83 while the mean scores of post-test in experimental class is 83.5. Based on the criteria of hypothesis test that if sig. 2 tailed (p) was lower than alpha (α) 0.05, the Ho (Null Hypothesis) was rejected and Ha (Alternative Hypothesis) was accepted. In this study, the result of sig. 2 tailed was 0.000 and it proved that p<α . It showed that there is a significant Effect of Using Online Articles on Students’ Reading Skill.